1983
DOI: 10.1007/bf00127496
|View full text |Cite
|
Sign up to set email alerts
|

G-banding homologies of some Australian rodents

Abstract: G-banding comparisons of 26 species in l0 genera of three tribes of Australian rodents show that at least one representative of each of the three tribes has autosomal complements that are indistinguishable on G-banding, implying unusually high conservation of karyotypes. Three genera (Pseudomys. Notomys, and Mastacomys) are distinguished karyotypically by a reciprocal translocation, one genus (Uromys) by a tandem fusion, and one genus (Zyzomys) by a radically altered karyotype. The only other rearrangements id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…(1983) and Koop et al (1984) used the largest 14 autosomal pairs shared with Peromyscus in a cladistic analysis of some muroid rodents. Many other studies used only chromosomal arms identified by G-banding in two or more of the taxa examined (e.g.. Baverstock et al, 1982Baverstock et al, . 1983Hood et al, 1984;Baker et al, 1987b).…”
mentioning
confidence: 99%
“…(1983) and Koop et al (1984) used the largest 14 autosomal pairs shared with Peromyscus in a cladistic analysis of some muroid rodents. Many other studies used only chromosomal arms identified by G-banding in two or more of the taxa examined (e.g.. Baverstock et al, 1982Baverstock et al, . 1983Hood et al, 1984;Baker et al, 1987b).…”
mentioning
confidence: 99%
“…Speciation without karyotypic change has been reported in a variety of mammalian taxa, including rodents (Baverstock et al, 1983), felids (Wurster-Hill and Gray, 1973), seals (Arnason, 1977), bats (Bickham et al, 1986), primates (Dutrillaux, 1979), cetaceans (Arnason. 1972, and marsupials (Rofe, 1979: Rofe andHayman, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Phallic morphology was described by Lidicker (1968Lidicker ( , 1973Lidicker and Brylski, 1987; the specimens dissected, AMNH 191406 and 194940, were identified as L. elegans, but are actually examples of L. ernstmayri). Donnellan (1989) sampled the karyotype (2n 5 48) for L. elegans, which differs from the postulated ancestral Australo-Papuan murine karyotype (see Baverstock et al, 1983, and references cited there), excluding Rattus, by the presence of a pair of submetacentrics. Spermatozoan morphology and its significance were discussed by Breed (1997Breed ( , 2004 and Breed and Aplin (1994), who sampled both L. elegans and L. ernstmayri.…”
Section: Characteristics Of the Genusmentioning
confidence: 99%